Characterization of Thromboxane A2/Prostaglandin H2 Receptors in Porcine Coronary Artery -The Inhibitory Effect of a Novel Dibenzoxepin Derivative, KW-3635 - Miki, Ichiro; Ishii, Akio (Thrombosis and Haemostasis, 1992)
We characterized the thromboxane A2/prostaglandin H2 receptors in porcine coronary artery. The binding of [3H]SQ 29,548, a thromboxane A2 antagonist, to coronary arterial membranes was saturable and displaceable. Scatchard analysis of equilibrium binding showed a single class of high affinity binding sites with a dissociation constant of 18.5 ±1.0 nM and the maximum binding of 80.7 ± 5.2 fmol/mg protein. [3H]SQ 29,548 binding was concentration-dependently inhibited by thromboxane A2 antagonists such as SQ 29,548, BM13505 and BM13177 or the thromboxane A2 agonists such as U46619 and U44069. KW-3635, a novel dibenzoxepin derivative, concentration-dependently inhibited the [3H]SQ 29,548 binding to thromboxane A2/prosta-glandin H2 receptors in coronary artery with an inhibition constant of 6.0 ± 0.69 nM (mean ± S.E.M.).